THE ENHANCEMENTS OF NUMERACY THROUGH THE FLAVELL’S PRINCIPAL IN THE COGNITIVE ‘S DEVELOPMENT FOR THE CHILDREN IN TK B SRIJAYA KM 5,5 PALEMBANG - SYAFDANINGSIH SYAFDANINGSIH (Sriwijaya University Learning and Education International Conference, 2016)
This research of class’ action is occurred in TK Srijaya Km 5,5 Palembang with the participants of 25 children. With a problem formulation: “Is it possible for the use of Flavell’s Principal in numeracy: 1) could increasing the children’s motivation for studying? 2) increasing the numeracy of the children?”. This research is aimed for increasing the motivation of studying and the numeracy for the cognitive development of children in TK B Srijaya Palembang. The data collecting are the observation and test for each cycle. At the first cycle, achieved for 60 score, and the average ability of children’s numeracy is 50 with the deficient category, for eleven children or 44%. The weaknesses of first cycle are: the lack of children’s motivation for studying, the lack of curiosity and confidence. In numeracy, there was a child who repeated the specific number and skip the other numbers, so he couldn’t able to say the numbers of things which has been counted. Therefore, this condition is fixed in the second cycle by giving the verbal or non verbal enhancements and the various playing activities and more motivations, so it could reached for the good category for 18 children (72%) with average score 70 or the numeracy is 66 with good category for 16 children or 64%. The weakness of this cycle is “The abstraction principle and The Order Irrelevance Principle” where the children were still not confident for doing the task. So, the children couldn’t differ the countable things and uncountable things like water, sand, flour. And, the children couldn’t represent the things that has been counted as the ordinal symbol of numbers which has been said. This thing is fixed in the third cycle as by giving the maximum motivation and giving the various playing facilities, so the children are motivated for doing the task. It has been proved in the 3rd cycle, as 21 children (87,5%) who are in the good minimum category (score >= 70) and the average numeracy in the good minimum category (score>= 60) as 20 children (83,33%). Therefore, in TK Srijaya Palembang is suggested for apply the Flavell principal for counting learninf of cognitive development.